2011
DOI: 10.1590/s0102-09352011000300014
|View full text |Cite
|
Sign up to set email alerts
|

Altos níveis de fitase em rações para frangos de corte

Abstract: RESUMOAvaliaram-se o desempenho, o coeficiente de digestibilidade da matéria seca (CDMS), da proteína bruta (CDPB), a retenção aparente de cálcio (Ca) e fósforo (P) e a energia metabolizável aparente corrigida para balanço de nitrogênio (EMAn) de dietas suplementadas com altos teores de fitase (FTU) para frangos, até 35 dias de idade. Foram utilizados 1848 pintos, distribuídos em delineamento inteiramente ao acaso, com sete tratamentos e oito repetições de 35 aves. Os tratamentos foram: T1: dieta-controle; T2:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…Those authors found improved nutrient digestibility with an enzymatic combination of phytase and a complex containing amylase, xylanase, and protease, in broiler diets. Meneghetti et al (2011) worked with phytase supplementation at levels starting at 450 mg.kg -1 diet with a nutritional reduction in the dietary energy and concluded that it can be used in broilers from 1 to 35 days of age without any harm to their nutrient digestibility and energy utilization. Liebert et al (2005) experimented phytase supplementation (300 mg.kg -1 ) in corn-and soybean mealor wheat bran-and soybean meal-based diets for commercial layers and found no effect on their intake, retention, and excretion of phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…Those authors found improved nutrient digestibility with an enzymatic combination of phytase and a complex containing amylase, xylanase, and protease, in broiler diets. Meneghetti et al (2011) worked with phytase supplementation at levels starting at 450 mg.kg -1 diet with a nutritional reduction in the dietary energy and concluded that it can be used in broilers from 1 to 35 days of age without any harm to their nutrient digestibility and energy utilization. Liebert et al (2005) experimented phytase supplementation (300 mg.kg -1 ) in corn-and soybean mealor wheat bran-and soybean meal-based diets for commercial layers and found no effect on their intake, retention, and excretion of phosphorus.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended phytase dosage for broiler diets is 500 FTU/kg (Phytase Unit), while the Superdosing concept of phytase is the addition of higher levels of this enzyme in the diets, being double or triple the usual value (Meneghetti et al, 2011;Dersjant-Li et al, 2015;). Research has reported that phytase superdosing has beneficial effects on animal performance (Cowieson et al, 2011;Pirgozliev et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The NAPs are not digested and also impair the digestion and absorption of other nutrients because they hydrate and increase the viscosity of the digesta, impairing thus the activity of endogenous enzymes and the absorption of simple molecules, such as glucose and free amino acids (4) . The supplementation of exogenous enzymes to the diet improves the production efficiency of birds as it increases the digestion of low-quality products and reduces the loss of nutrients in the feces (5)(6)(7) .…”
Section: Introductionmentioning
confidence: 99%